2020
DOI: 10.26508/lsa.202000700
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin expression in the endoplasmic reticulum shapes the metabolic fitness of B lymphocytes

Abstract: The major function of B lymphocytes is to sense antigens and to produce protective antibodies after activation. This function requires the expression of a B-cell antigen receptor (BCR), and evolutionary conserved mechanisms seem to exist that ensure that B cells without a BCR do not develop nor survive in the periphery. Here, we show that the loss of BCR expression on Burkitt lymphoma cells leads to decreased mitochondrial function and impaired metabolic flexibility. Strikingly, this phenotype does not result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…OCR and ECAR were measured using Seahorse flux technology. Experiments were performed as described before ( 48 ). Detailed protocols are included in SI Appendix , Methods .…”
Section: Methodsmentioning
confidence: 99%
“…OCR and ECAR were measured using Seahorse flux technology. Experiments were performed as described before ( 48 ). Detailed protocols are included in SI Appendix , Methods .…”
Section: Methodsmentioning
confidence: 99%
“…The maintenance of endoplasmic reticulum (ER) homeostasis shapes B-cell metabolism and metabolic stress responses by regulating mitochondrial calcium levels. 16 To further investigate the effect of SARS-CoV-2 infection on B-cell metabolism, B cells from patients and healthy controls were stimulated with F(ab′) 2 anti-human Ig(M + G) for varying times, stained with ER tracker and MITO tracker of mitochondria, and analyzed by confocal microscopy. We found that MFI of ER and MITO of patient B cell significantly increased at 0 and 5 min, but decreased at 30 min compared to that of healthy controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BCL-2 expression can decrease apoptosis of GC B cells by 10-fold (45) but is insufficient to prevent apoptosis due to deleterious mutations induced in BCR genes (43). Jumaa et al discovered a mechanism by which BCR expression regulates the metabolism of B cells in a BCR signaling independent manner (46). According to this mechanism, BCR regulates changes in endoplasmic reticulum that in turn controls mitochondrial activity.…”
Section: Gc B Cell Apoptosismentioning
confidence: 99%
“…Jumaa et al. discovered a mechanism by which BCR expression regulates the metabolism of B cells in a BCR signaling independent manner ( 46 ). According to this mechanism, BCR regulates changes in endoplasmic reticulum that in turn controls mitochondrial activity.…”
Section: Regulation Of B Cell Fates In the Gcsmentioning
confidence: 99%
See 1 more Smart Citation